The Relationship Between Climate Risk Disclosure and Performance on Mining Companies: Evidence From A Developing Economy - MATEMANE, Reon; GRACA, Nikita (PT Keberlanjutan Strategis Indonesia, 2023)
The main aim of this study is to develop an unweighted climate risk disclosure index to assess whether climate risk disclosure predicts mining companies’ performance.The catastrophic nature of climate risk has become more topical in recent years. Yet, academic research efforts have been directed to climate risk from the perspective of developed economies only and very little is understood about it in developing economies. 216 firm observations in mining sector for the period covering 2016 through 2021 were analysed using descriptive statistics and estimated generalised least square with period seemingly unrelated regression. The results suggest that the climate risk disclosure is significant in predicting company performance as proxied by earnings per share (EPS), economic value added (EVA) and return on equity (ROE). Policy makers and regulators should encourage companies to intensify climate risk disclosure so as to maximise value and benefit relevant stakeholders. The study contributes to the ongoing debates on climate risk by focusing on extractive industry, mining sector in a developed economy setting. Methodologically, the study developed an unweighted disclosure checklist that can guide companies on pertinent climate risk issues to disclose.